2014
DOI: 10.23986/afsci.41329
|View full text |Cite
|
Sign up to set email alerts
|

Use of faba beans (Vicia faba L.) in diets of laying hens

Abstract: The study was conducted to evaluate an appropriate inclusion level of locally produced unprocessed or expander-processed coloured flowered faba bean (FB) (cv. 'Kontu') seeds in diets for laying hens. Egg production and egg quality variables were determined with 560 hens (Lohmann Selected Leghorn, LSL Classic) in a 40-week continued experiment. The hens were fed one of the five diets containing soybean meal as the main protein source. A diet without FB was served as a control diet. Both unprocessed and expander… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 20 publications
5
18
0
Order By: Relevance
“…With 24% faba beans, the authors noticed reduced weight gain in finishing broilers compared to the group with only 18% faba beans. Koivunen et al [37] also observed lower bodyweight and reduced feed consumption with 24% faba beans in the diet compared to a soybean-based control. In contrast, another study found that even the feeding of 50% faba beans in the ration did not affect weight development, feed intake, dressing percentage and the weights of breasts and legs [38].…”
Section: Discussionmentioning
confidence: 92%
“…With 24% faba beans, the authors noticed reduced weight gain in finishing broilers compared to the group with only 18% faba beans. Koivunen et al [37] also observed lower bodyweight and reduced feed consumption with 24% faba beans in the diet compared to a soybean-based control. In contrast, another study found that even the feeding of 50% faba beans in the ration did not affect weight development, feed intake, dressing percentage and the weights of breasts and legs [38].…”
Section: Discussionmentioning
confidence: 92%
“…Since soybean and palm oil employed as ingredients in the fodder used in the farm are mainly responsible for the impacts caused by hen feeding, the first environmental improvement that should be tried is the total or partial replacement of these ingredients in the fodder formulations. For instance, pea or bean can be employed instead of soybean, since both these crops have been tested successfully as ingredients in laying hen feed formulation (Koivunen et al, 2014;Koivunen et al, 2015). In the same way, palm oil could be substituted with other crop oils such as cotton, corn, flax, canola, olive or sunflower oils, which are often employed as components of fodders for laying hens (Balevi and Coskun, 2000;Ceylan et al, 2011, Yuan et al, 2014.…”
Section: Improvement Actionsmentioning
confidence: 99%
“…Not all findings are conclusive and appear to depend on the antinutritional characteristics of FB as well as bird physiological development [17]. For example, Laudadio et al [21] and DĂ€nner et al [20] find that FB can be included in laying hens' diets without having a significant negative effect on laying performance or egg quality; however, it was found in [22] that the inclusion of FB in laying hens' diets can decrease egg weight. In addition, broiler nutrition (apparent metabolizable energy; AMEn) values are found to be adversely affected by antinutritional factors in FB; however, adult cockerels appear to be more resilient towards antinutritional factors [17].…”
Section: Introductionmentioning
confidence: 99%